ANALISIS TINGKAT PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI DI KABUPATEN GRESIK - Atifatur Rakhmawati; Arfida Boedirochminarni (Jurnal Ilmu Ekonomi JIE, 2018)
Labor plays an important role in the establishment of a company. The number of companies or industries is also a driver of economic growth. The purpose of this research is to analyze the influence of Minimum Wages of District (UMK), the number of industries, and the population of the labor force on the absorption of manpower of industrial sector in the sub-districts Gresik regency in 2007-2015. The results obtained in this study is stated that the variable Minimum Wage District (UMK) and the population of the workforce have a positive and significant effect on the absorption of industrial sector workforce in Gresik regency, while the variable of the number of industries has a negative and significant effect on the absorption of manpower of industrial sector in sub-districts Gresik regency.Keywords: Employment, Wage, Industry.